Heterostructure austenitic stainless steel and method for producing the same
Patent Information
- Application Number
- CN202611335011.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-11-03
AI Technical Summary
Existing austenitic stainless steels have insufficient wear resistance in marine environments and low surface hardness. Conventional surface strengthening methods are difficult to achieve good corrosion and wear resistance on large-size plates, and the processes are complex and costly.
Heterogeneous austenitic stainless steel with a mixed nano/ultrafine grain structure was constructed by cold rolling and annealing processes. By controlling the cold rolling temperature and annealing parameters, a specific ratio of micron-sized, submicron-sized, and nano-sized crystals was formed, thus producing heterogeneous austenitic stainless steel with both high strength and good plasticity.
It significantly improves the corrosion and wear resistance of austenitic stainless steel, breaks through the bottleneck of traditional material strength and corrosion and wear resistance, is suitable for the industrial production of large-size plates, and has excellent comprehensive mechanical properties.
Smart Images

Figure CN123027397A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of stainless steel preparation, and particularly relates to a heterogeneous structure austenitic stainless steel and a preparation method thereof, and particularly relates to a preparation method for significantly improving the corrosion and wear performance of austenitic stainless steel by constructing a heterogeneous structure nano / sub-fine grain structure. BACKGROUND
[0002] Austenitic stainless steel has become an indispensable structural material in the field of marine engineering equipment due to its excellent seawater corrosion resistance, good cold and hot working performance, and weldability, and is currently widely used in key equipment such as seawater desalination devices, offshore oil and gas exploitation platforms, ship power systems, and deep-sea exploration instruments. However, the yield strength of such austenitic stainless steel is usually only 200-300 MPa, and the surface hardness is relatively low, about 190 HV. Under actual service conditions such as sand erosion, mechanical vibration, and fluid impact, its wear resistance is obviously insufficient, and a large number of parts fail prematurely due to surface wear, which seriously restricts the safety and service life of the equipment. Therefore, how to improve the wear resistance of austenitic stainless steel while maintaining its excellent corrosion resistance is an important topic in the research of marine engineering materials.
[0003] Grain refinement is an effective strengthening method to improve the strength and hardness of metal materials. Research shows that uniform sub-fine grain structure with a grain size of nanometer to sub-micron can significantly improve the yield strength and hardness. However, uniform sub-fine grain structure often faces the inherent defects of insufficient plasticity reserve and decreased work hardening capacity, and is prone to early fracture under complex stress, which is difficult to meet the comprehensive demand of toughness and reliability of engineering structure. Although the construction of heterogeneous structure in austenitic stainless steel is expected to improve the above mechanical property contradiction, its damage behavior under the coupling service environment of seawater corrosion and wear is still lacking of systematic research.
[0004] In actual seawater working conditions, the surface of stainless steel material not only suffers mechanical cutting and plowing action of the counter-wear part, but also faces the threat of pitting and crevice corrosion caused by chloride ions. Its corrosion and wear process is much more complex than pure corrosion or wear: wear will continuously remove the surface passivation film, expose fresh active metal, and accelerate electrochemical dissolution; and the brittle product or pit produced by corrosion will further aggravate the stress concentration and material spalling of the friction surface, and the two promote each other, often leading to a material loss rate much higher than that of single corrosion and single wear damage.
[0005] In the prior art, in order to improve the wear resistance and corrosion resistance of the surface of the austenitic stainless steel, surface mechanical grinding, ion implantation, laser cladding and low-temperature nitriding and other surface strengthening means are often used. These technologies can form a hardened layer or a modified layer on the surface of the stainless steel, but usually have problems such as limited treatment layer depth, long process cycle, high equipment cost and uneven treatment of complex-shaped parts, and are difficult to meet the batch production requirements of large-size plates or structural parts. Therefore, how to make the austenitic stainless steel have good corrosion and wear resistance is a technical problem to be solved in the field. SUMMARY
[0006] The present application aims at the technical problem that the existing surface strengthening means is difficult to make the bulk austenitic stainless steel body have good corrosion and wear resistance, and proposes a heterogeneous structure austenitic stainless steel and a preparation method thereof. The method is simple to operate, can prepare bulk heterogeneous structure materials with nano / superfine grain mixed structure, is easy to industrialize, can significantly improve the corrosion and wear resistance of the austenitic stainless steel, and provides necessary technical support for the popularization and application of new high-strength austenitic stainless steel in marine engineering equipment.
[0007] In order to achieve the above purpose, the technical scheme adopted by the present application is as follows: a preparation method of a heterogeneous structure austenitic stainless steel, comprising the following steps: Cold rolling step: the austenitic stainless steel plate is subjected to multi-pass cold rolling deformation, the rolling temperature is-50℃~25℃, and the total rolling deformation is 60%~86%; Annealing step: the cold-rolled austenitic stainless steel plate is subjected to annealing treatment, the annealing temperature is 650℃~750℃, the annealing time is 5~60min, and then air cooling to room temperature to obtain the heterogeneous structure austenitic stainless steel.
[0008] It is understood that, based on actual circumstances, those skilled in the art can adjust the rolling temperature, total rolling deformation, annealing temperature, and annealing time within the above range. For example, the rolling temperature can also be -50℃, -45℃, -40℃, -35℃, -30℃, -25℃, -20℃, -15℃, -10℃, -5℃, 0℃, 5℃, 10℃, 15℃, 20℃, 25℃, or any point value within the above range; the total rolling deformation can also be 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%, or 76%. 78%, 80%, 82%, 84%, 86%, or any value within the above range; the annealing temperature can also be 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, or any value within the above range; the annealing time can also be 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min, or any value within the above range.
[0009] In one embodiment, the austenitic stainless steel plate is a metastable 304 austenitic stainless steel plate, which, by mass percentage, consists of the following chemical composition: C≤0.08%, Si≤1.0%, Mn≤2.0%, Cr: 17.0%~20.0%, Ni: 7.0%~10.0%, N≤0.1%, Cu≤0.30%, with the balance being Fe and unavoidable impurities.
[0010] In one embodiment, during the cold rolling step, the austenitic stainless steel plate is immersed in a cooling medium for heat preservation and cooling before each cold rolling pass. The cooling medium is a mixture of ethanol and liquid nitrogen, the temperature of the cooling medium is -50℃ to -10℃, and the heat preservation and cooling time is 1 minute.
[0011] In one embodiment, the total deformation during the cold rolling step is 65% to 86%.
[0012] In one embodiment, the cold rolling deformation per pass is 0.1 mm.
[0013] In one embodiment, the annealing step is performed using a box-type resistance furnace.
[0014] In one embodiment, the annealing time in the annealing step is 10-50 minutes.
[0015] In another aspect, the present invention provides a heterostructure austenitic stainless steel, which is prepared by any of the above-described methods for preparing heterostructure austenitic stainless steel.
[0016] In one embodiment, the microstructure of the heterostructure austenitic stainless steel is composed of nanocrystals, submicron crystals and micron crystals, wherein the total proportion of nanocrystals and submicron crystals is 70% to 85% and the proportion of micron crystals is 15% to 30%.
[0017] In one embodiment, the heterostructure austenitic stainless steel has a yield strength of 700~1100MPa, a tensile strength of 800~1200MPa, a uniform elongation of 25%~60%, and a Vickers hardness of 260~350HV10.
[0018] Compared with the prior art, the advantages and positive effects of the present invention are as follows: (1) The method for preparing heterogeneous austenitic stainless steel of the present invention can precisely control the proportion and size of nanocrystals, submicron crystals and micron crystals in the heterogeneous structure by adjusting the total deformation of cold rolling, cold rolling temperature and annealing parameters, so as to achieve the customized corrosion and wear performance as needed. The process of the present invention is simple to operate and overcomes the shortcomings of surface treatment technologies such as surface mechanical grinding, ion implantation and laser cladding, such as limited gradient layer thickness, complex process and long processing time. It is suitable for the preparation of large-size plates and can prepare large-size block austenitic stainless steel with good mechanical properties and corrosion and wear performance, which is easy to realize industrial production. The heterogeneous austenitic stainless steel prepared by the method of the present invention has high strength, good plasticity and excellent corrosion resistance, breaking through the bottleneck of mutual restriction between strength and corrosion and wear resistance of traditional materials.
[0019] (2) The heterostructure austenitic stainless steel of the present invention is a heterostructure structure composed of micron-sized, submicron-sized and nano-sized crystals mixed in a specific ratio. In a 3.5% NaCl solution environment, the corrosion wear rate is significantly lower than that of conventional coarse-grained austenitic stainless steel, showing excellent corrosion wear performance. Attached Figure Description
[0020] Figure 1 Images showing the metallographic structure of the original steel plate in Example 1; Figure 2 The image shows an EBSD image of the heterogeneous nano / ultrafine grain structure obtained by cold rolling and annealing steel in Example 1. Figure 3 The stress-strain curve of the heterostructured nano / ultrafine crystalline austenitic stainless steel after treatment in Example 1 is shown. Figure 4 The image shows the three-dimensional morphology of the wear marks after corrosion and wear of the heterostructured nano / ultrafine crystalline austenitic stainless steel treated in Example 1. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Existing 304 austenitic stainless steel suffers from low strength and hardness due to its coarse grains, resulting in insufficient corrosion and wear resistance in seawater environments. To address the technical problem that existing surface strengthening methods cannot achieve good corrosion and wear resistance in bulk austenitic stainless steel, this invention provides a method for preparing heterogeneous austenitic stainless steel. Using commercially available metastable 304 austenitic stainless steel as raw material, by controlling the cold rolling temperature, deformation amount, and subsequent annealing parameters, a multi-scale heterogeneous nano / ultrafine-grained austenitic stainless steel with nanocrystals, submicron crystals, and micron crystals is constructed within the material, significantly improving the corrosion and wear resistance of austenitic stainless steel in seawater environments.
[0023] The method for preparing heterogeneous austenitic stainless steel according to embodiments of the present invention includes the following steps: Cold rolling step: Austenitic stainless steel sheets are subjected to multi-pass cold rolling deformation at a rolling temperature of -50℃ to 25℃, with a total deformation of 60% to 86%. This step induces martensitic phase transformation through deformation, resulting in rolled sheets containing different proportions of martensite and retained austenite. Within this temperature range, spontaneous martensitic phase transformation does not occur in austenitic stainless steel during cold rolling deformation. Even at 50℃, there is enough driving force to completely transform austenite into martensite when deformed. Annealing Steps: The cold-rolled 304 austenitic stainless steel sheet is placed in a box-type resistance furnace for annealing at a temperature of 650℃~750℃ for a holding time of 5~60 min, preferably 10~50 min. It is then air-cooled to room temperature to obtain a heterogeneous austenitic stainless steel. During the annealing process, annealing at 650~750℃ and holding for 5~60 min effectively induces the inverse phase transformation and partial recrystallization of martensite induced by cold rolling deformation, forming a heterogeneous structure where nano / ultrafine and micron-sized grains coexist. Grain size and phase composition can be precisely controlled by adjusting the temperature and time.
[0024] In the above steps of the present invention, by adjusting the cold rolling deformation amount and annealing parameters, a heterogeneous nano / ultrafine crystalline structure composed of nanocrystals, submicron crystals and micron crystals can be obtained.
[0025] In the cold rolling step of this invention, the austenitic stainless steel plate is a metastable 304 austenitic stainless steel plate. By mass percentage, the metastable 304 austenitic stainless steel is composed of the following chemical composition: C≤0.08%, Si≤1.0%, Mn≤2.0%, Cr:17.0%~20.0%, Ni:7.0%~10.0%, N≤0.1%, Cu≤0.30%, with the balance being Fe and unavoidable impurities.
[0026] In a preferred embodiment of the present invention, during the cold rolling step, the austenitic stainless steel plate is immersed in a cooling medium for heat preservation and cooling before each cold rolling pass. The cooling medium is a mixture of ethanol and liquid nitrogen, and the temperature of the cooling medium is adjusted to -50°C to -10°C by controlling the ratio of ethanol to liquid nitrogen. The heat preservation and cooling time is 1 minute. Immersing the austenitic stainless steel plate in the cooling medium for heat preservation and cooling before each cold rolling pass can precisely control the plate temperature before rolling, effectively suppress dynamic recovery, and promote deformation-induced martensitic phase transformation, thereby obtaining a high dislocation density and martensitic structure.
[0027] In a preferred embodiment of the present invention, the total rolling deformation is 65% to 86%.
[0028] In a preferred embodiment of the present invention, the cold rolling deformation per pass is 0.1 mm. By controlling the cold rolling deformation per pass, small deformations can be accumulated successively, ensuring uniform deformation and stable rolling force in each pass. This is beneficial for accurately controlling the total deformation and sheet shape accuracy, and reducing edge cracks and surface defects caused by large single deformations.
[0029] This invention also provides a heterostructured austenitic stainless steel, prepared by the aforementioned method, which exhibits excellent mechanical properties and corrosion and wear resistance, meeting the comprehensive service requirements of marine engineering equipment for structural materials requiring high strength, toughness, and wear resistance. This invention constructs a heterostructure within austenitic stainless steel, composed of micron-, submicron-, and nano-crystalline structures. The softer micron-crystalline regions are surrounded by harder ultrafine-grained regions. During deformation, the plastic incompatibility between the soft and hard regions generates a significant strain gradient, leading to the accumulation of numerous geometrically necessary dislocations near the interface, forming a back stress strengthening effect. This allows the material to achieve high strength and hardness while retaining good plasticity and work hardening ability, overcoming the limitation of the inverse relationship between strength and plasticity in traditional fine-grained materials.
[0030] The microstructure of the heterostructure austenitic stainless steel of this invention consists of nanocrystals, submicron crystals, and micron crystals. The grain size of the nanocrystals and submicron crystals is less than 1 μm, while the grain size of the micron crystals is greater than 1 μm. The total proportion of nanocrystals and submicron crystals is 70%–85%, and the proportion of micron crystals is 15%–30%. The heterostructure austenitic stainless steel exhibits a yield strength of 700–1100 MPa, a tensile strength of 800–1200 MPa, a uniform elongation of 25%–60%, and a Vickers hardness of 260–350 HV10. Furthermore, the corrosion wear rate of the heterostructure austenitic stainless steel in a 3.5% (w / w) NaCl solution environment is significantly lower than that of coarse-grained austenitic stainless steel, demonstrating excellent corrosion wear performance.
[0031] Through the description of several embodiments of the heterostructure austenitic stainless steel and its preparation method of the present invention, it can be seen that the heterostructure austenitic stainless steel and its preparation method of the present invention have at least one or more of the following advantages: 1. Highly controllable structure: By adjusting the cold rolling deformation, cold rolling temperature and annealing parameters, this invention can precisely control the proportion and size of nanocrystals, submicron crystals and micron crystals in heterogeneous structures, and achieve on-demand customization of corrosion and wear performance.
[0032] 2. Good process compatibility, suitable for large-size bulk materials: The preparation method of this invention is simple and efficient, and is suitable for the preparation of large-size plates. It overcomes the shortcomings of surface treatment technologies such as surface mechanical grinding, ion implantation, and laser cladding, such as limited gradient layer thickness, complex process, and long processing time, and is easy to realize industrial production.
[0033] 3. Significantly improved corrosion and wear performance: The heterostructure austenitic stainless steel prepared by this invention exhibits a significantly lower corrosion and wear rate in a 3.5% NaCl solution environment than conventional coarse-grained austenitic stainless steel, demonstrating excellent corrosion and wear performance.
[0034] 4. Excellent comprehensive performance of high plasticity and corrosion and wear resistance: The heterostructure austenitic stainless steel prepared by this invention has high strength, good plasticity and excellent corrosion resistance, breaking through the bottleneck of mutual restriction between strength and corrosion and wear resistance of traditional materials.
[0035] To provide a clearer and more detailed description of the heterostructure austenitic stainless steel and its preparation method provided in the embodiments of the present invention, the following description will be based on specific embodiments.
[0036] Example 1 The following equipment is used in this embodiment: the cold rolling mill is a φ325×400mm four-roll direct-draw reversible cold rolling mill; the annealing furnace is a box-type resistance furnace for heat treatment; and the friction and wear testing machine is an RTECMFT-5000 friction and wear performance testing machine. The raw material is metastable 304 austenitic stainless steel plate, which, by mass fraction, consists of the following chemical composition: C 0.04%, Si 0.39%, Mn 1.09%, Cr 17.94%, Ni 7.92%, Cu 0.0379%, N 0.047%, with the remainder being Fe and unavoidable impurities. The original thickness of the metastable 304 austenitic stainless steel plate is 4.5 mm, and the grain size is 24 μm. The metallographic structure of the original steel plate is shown in the image below. Figure 1 As shown. By Figure 1 It can be seen that the original state of austenitic stainless steel has equiaxed austenitic grains with an average grain size of approximately 24µm.
[0037] The preparation method of heterogeneous austenitic stainless steel in this embodiment includes the following steps: Cold rolling process: A 100mm × 150mm rectangular strip is cut from the original metastable 304 austenitic stainless steel plate, with the length direction of the strip aligned with the rolling direction. The cut strip is completely immersed in a mixture of ethanol and liquid nitrogen, and the temperature of the mixture is maintained at -50℃ by adjusting the ratio. The mixture is held at this temperature for 1 minute, and the temperature of the mixture is monitored in real time using thermocouples during the cooling process. Under this temperature condition, the strip is cold rolled in multiple passes using a cold rolling mill, with each pass reducing the thickness by 0.1mm, resulting in a total reduction rate of 83%. The final thickness of the steel plate after rolling is 0.79mm. Annealing step: The temperature of the heat treatment box-type resistance furnace is raised to 660℃ beforehand. Then, the metastable 304 austenitic stainless steel plate that has completed low-temperature cold rolling is placed in the box-type resistance furnace and held for 50 minutes. After that, it is taken out and air-cooled to room temperature to obtain heterostructure austenitic stainless steel.
[0038] The microstructure of 304 austenitic stainless steel after cold rolling and annealing is as follows: Figure 2 As shown, the microstructure obtained in this embodiment is mainly composed of equiaxed austenitic grains with an average grain size of 500 nm, with a small amount of untransformed strain-induced martensite remaining in the microstructure.
[0039] Comparative Example 1 The untreated metastable 304 austenitic stainless steel sheet, by mass fraction, consists of the following chemical composition: C 0.04%, Si 0.39%, Mn 1.09%, Cr 17.94%, Ni 7.92%, Cu 0.0379%, N 0.047%, with the remainder being Fe and unavoidable impurities.
[0040] Performance testing Mechanical property tests were conducted on the heterostructure austenitic stainless steel prepared in Example 1, and the corresponding engineering stress-strain curves are shown below. Figure 3 As shown. By Figure 3It can be seen that the yield strength is 1053 MPa, the tensile strength is 1060 MPa, the elongation is 27%, and the hardness is 350 HV. It is evident that the heterostructure austenitic stainless steel prepared in this embodiment has excellent comprehensive mechanical properties.
[0041] The reference standards for the above performance tests are as follows: yield strength, tensile strength and elongation are tested according to the American standard ASTM E8-04; hardness is tested according to GB / T 4340.1-2024.
[0042] The heterostructured austenitic stainless steel prepared in Example 1 and the untreated metastable 304 austenitic stainless steel plate from Comparative Example 1 were placed in a 3.5% (w / w) NaCl solution for corrosion and wear comparison experiments. A reciprocating ball-plate contact friction and wear tester was used, with Si3N4 balls as the grinding balls. The normal load was set to 30 N, the reciprocating frequency to 5 Hz, and the total wear test duration to 60 min. Corrosion electrochemical testing was performed using a standard three-electrode system, and potentiodynamic polarization curves were measured during the wear process.
[0043] Three-dimensional morphology images of the samples after corrosion and wear in Example 1 and Comparative Example 1 are shown below. Figure 4 As shown. Test results indicate that the heterostructure austenitic stainless steel prepared in Example 1 exhibits a corrosion wear volume of 4.03 × 10⁻⁶ m³ in a 3.5% NaCl solution. 6 μm 3 The wear volume was significantly lower than that of the original coarse-grained sample (8.33 × 10⁻⁶) under the same conditions. 6 μm 3 Example 1 shows superior corrosion and wear performance compared to the original coarse-grained state.
[0044] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Any modifications, alterations, evolutions, or improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope of the present invention.
Claims
1. A method for preparing heterogeneous austenitic stainless steel, characterized in that, Includes the following steps: Cold rolling process: The austenitic stainless steel sheet is subjected to multiple cold rolling deformations at a rolling temperature of -50℃ to 25℃, with a total rolling deformation of 60% to 86%. Annealing process: The cold-rolled austenitic stainless steel sheet is annealed at a temperature of 650℃~750℃ for 5~60 minutes, and then air-cooled to room temperature to obtain austenitic stainless steel with a heterostructure.
2. The method for preparing heterogeneous austenitic stainless steel according to claim 1, characterized in that, The austenitic stainless steel plate is a metastable 304 austenitic stainless steel plate, which, by mass percentage, consists of the following chemical composition: C≤0.08%, Si≤1.0%, Mn≤2.0%, Cr: 17.0%~20.0%, Ni: 7.0%~10.0%, N≤0.1%, Cu≤0.30%, with the balance being Fe and unavoidable impurities.
3. The method for preparing heterogeneous austenitic stainless steel according to claim 1, characterized in that, In the cold rolling step, before each cold rolling pass, the austenitic stainless steel plate is immersed in a cooling medium for heat preservation and cooling. The cooling medium is a mixture of ethanol and liquid nitrogen, the temperature of the cooling medium is -50℃ to -10℃, and the heat preservation and cooling time is 1 minute.
4. The method for preparing heterogeneous austenitic stainless steel according to claim 1, characterized in that, In the cold rolling step, the total deformation during rolling is 65% to 86%.
5. The method for preparing heterogeneous austenitic stainless steel according to claim 1, characterized in that, In the cold rolling process, the deformation amount for each cold rolling pass is 0.1 mm.
6. The method for preparing heterogeneous austenitic stainless steel according to claim 1, characterized in that, In the annealing step, a box-type resistance furnace is used for annealing.
7. The method for preparing heterogeneous austenitic stainless steel according to claim 1, characterized in that, In the annealing step, the annealing time is 10~50 minutes.
8. A heterogeneous austenitic stainless steel, characterized in that, It is prepared by the method for preparing heterogeneous austenitic stainless steel according to any one of claims 1-7.
9. The heterogeneous austenitic stainless steel according to claim 8, characterized in that, The microstructure of the heterostructure austenitic stainless steel consists of nanocrystals, submicron crystals and micron crystals, with nanocrystals and submicron crystals accounting for 70% to 85% of the total and micron crystals accounting for 15% to 30%.
10. The heterogeneous austenitic stainless steel according to claim 8, characterized in that, The heterostructured austenitic stainless steel has a yield strength of 700~1100MPa, a tensile strength of 800~1200MPa, a uniform elongation of 25%~60%, and a Vickers hardness of 260~350HV10.
